Seeking the difference between starting and established PCI center - Yoga Yuniadi (The Indonesian Heart Association, 2011)
The study by Juwana et al is looking for primary PCI results that were conducted in a starting PCI center. The authors thought that as PCI results depend on center experience then it is mandatory to study how good it is when performed in a new or starting PCI center. The question arise is whether primary PCI re-sults would really be differed? If it is so, what make it difference? Some variables need to be elaborated in this regard that mainly comprised of operator, paramedics, tools and devices. Though a study by Politi et al suggest that expertise and experience of the whole professional team, rather than just of the individual operator, play a major role of PCI outcome, most of studies indicate the operator experience is the main issue. It is why that ACC/AHA guideline strictly stated that only operator who has sufficient experience i.e. 75 PCI per year allowed to do primary PCI. In ad-dition, it is recognized that there are limitations in the application of the risk-adjustment methodology in the evaluation of rare events and of low-volume operators, and that there might be substantial varia-tions in the volume–outcome relationship.